Reviews - Mortensen, Peter; Lind, Birgit (Journal of Danish Archaeology, 1990)
Reviews: O.M.C. Haex, H.H. Curvers & P.M.M.G. Akkermans ( eds.): To the Euphrates and Beyond (by Peder Mortensen) Magdalena Tempelmann-Maczynska: Die Perlen der romischen Kaiserzeit (by Birgit Lind)